2012
DOI: 10.3233/wor-2012-0559-3026
|View full text |Cite
|
Sign up to set email alerts
|

The effect on employees of violence climate in the workplace

Abstract: Violent incidents in the workplace which negatively affect employees' health and safety present an important problem of health and safety at work. This study aimed to determine the effects of the violence prevention climate on employees' job satisfaction and stress by determining how they perceive the dimensions of the violence climate. The participants in this study were 240 employees in various sectors (health, service, etc.) in Turkey. The study used the 18 item Violence Prevention Climate scale developed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…In the Palestinian territories, most doctors (80.4%) reported exposure to violence in the previous 12 months; 20.8% reported physical and 59.6% reported non-physical violence (Kitaneh & Hamdan, 2012). Workplace violence could directly increase the prevalence of psychological symptoms, such as interpersonal sensitivity and anxiety (Aytac & Dursun, 2012;Merecz, Drabek, & Moscicka, 2009). Without peaceful work environments or harmonious doctor-patient relationships, many doctors worry about their personal safety, and gradually feel discouraged about their professional value.…”
Section: Discussionmentioning
confidence: 99%
“…In the Palestinian territories, most doctors (80.4%) reported exposure to violence in the previous 12 months; 20.8% reported physical and 59.6% reported non-physical violence (Kitaneh & Hamdan, 2012). Workplace violence could directly increase the prevalence of psychological symptoms, such as interpersonal sensitivity and anxiety (Aytac & Dursun, 2012;Merecz, Drabek, & Moscicka, 2009). Without peaceful work environments or harmonious doctor-patient relationships, many doctors worry about their personal safety, and gradually feel discouraged about their professional value.…”
Section: Discussionmentioning
confidence: 99%
“…The latter issue is important to consider in that prior research has demonstrated that witnessing threatening events can produce the same level of negative outcome as being the target of violent acts (Alden, et al, 2008; Leblanc & Kelloway, 2002). Witnessing workplace violence may raise concern among counselors that they themselves may face this type of violence in the future (Aytaç & Dursun, 2012). Counselor demographics and treatment orientation are associated with experiencing workplace violence, providing some insight regarding those counselors that may be at higher risk and suggestions for training and mentorship.…”
Section: Discussionmentioning
confidence: 99%
“…It affects the victim's health, satisfaction with work and life, confidence, and causes emotional exhaustion and burnout (Budin et al 2013;Waschgler et al 2013). Victims feel depression, anxiety and work-related stress (Aytaç & Dursun 2012;Rodwell & Demir 2012). Therefore, it is very important that each individual be informed in advance how to react in the event of violence.…”
Section: Introductionmentioning
confidence: 99%